Effect of homeopathic remedies and gentamicin in diarrhea in piglets - Vidal F., Florangel (2017)
The study aimed to evaluate the effect of nux vomica, the homeopathic complex TratHo® cholera and Gentamicin 5% in the treatment of diarrhea in piglets. A total of 150 piglets of 5 days old that showed diarrhea in a pig unit in Camagüey, Cuba, were evaluated. The animals were distributed in three groups of 50 each. In group I, piglets were treated with nux vomica 30 CH in a dose of 5 drops sublingual every 12 h the 1st day and then every 24 h until the 5th day. In group II, piglets were treated with to TratHo® cholera 30 CH in a dose of 5 drops sublingual every 12 h the 1st day and then every 24 h until the 5th day. In group III, piglets were treated with gentamicin 5% intramuscularly, 2 to 4 mg/kg every 12 h for 5 days. In all cases, piglets were rehydrated with lactated Ringer’s solution intraperitoneally, using 100 to 300 ml depending of the degree of dehydration. The clinical evolution, appetite and dehydration were analyzed without observing significant differences between groups. However, the homeopathic therapy was effective and cheaper than the antibiotic treatment.